Comparative Genomics across Three Ensifer Species Using a New Complete Genome Sequence of the Medicago Symbiont Sinorhizobium (Ensifer) meliloti WSM1022 - Laura Baxter; Proyash Roy; Emma Picot; Jess Watts; Alex Jones; Helen Wilkinson; Patrick Schäfer; Miriam Gifford; Beatriz Lagunas (Microorganisms, 2021)
Here, we report an improved and complete genome sequence of Sinorhizobium (Ensifer) meliloti strain WSM1022, a microsymbiont of Medicago species, revealing its tripartite structure. This improved genome sequence was generated combining Illumina and Oxford nanopore sequencing technologies to better understand the symbiotic properties of the bacterium. The 6.75 Mb WSM1022 genome consists of three scaffolds, corresponding to a chromosome (3.70 Mb) and the pSymA (1.38 Mb) and pSymB (1.66 Mb) megaplasmids. The assembly has an average GC content of 62.2% and a mean coverage of 77X. Genome annotation of WSM1022 predicted 6058 protein coding sequences (CDSs), 202 pseudogenes, 9 rRNAs (3 each of 5S, 16S, and 23S), 55 tRNAs, and 4 ncRNAs. We compared the genome of WSM1022 to two other rhizobial strains, closely related Sinorhizobium (Ensifer) meliloti Sm1021 and Sinorhizobium (Ensifer) medicae WSM419. Both WSM1022 and WSM419 species are high-efficiency rhizobial strains when in symbiosis with Medicago truncatula, whereas Sm1021 is ineffective. Our findings report significant genomic differences across the three strains with some similarities between the meliloti strains and some others between the high efficiency strains WSM1022 and WSM419. The addition of this high-quality rhizobial genome sequence in conjunction with comparative analyses will help to unravel the features that make a rhizobial symbiont highly efficient for nitrogen fixation.